The effect of leg dominance and landing height on ACL loading among female athletes - Mokhtarzadeh, H.; Ewing, K.; Janssen, I.; Yeow, C. H.; Brown, N.; Vee Sin Lee, P. (Journal of Biomechanics, 2017)
Female athletes are more prone to anterior cruciate ligament (ACL) injury. A neuromuscular imbalance called leg dominance may provide a biomechanical explanation. Therefore, the purpose of this study was to compare the side-to-side lower limb differences in movement patterns, muscle forces and ACL forces during a single-leg drop-landing task from two different heights. We hypothesized that there will be significant differences in lower limb movement patterns (kinematics), muscle forces and ACL loading between the dominant and non-dominant limbs. Further, we hypothesized that significant differences between limbs will be present when participants land from a greater drop-landing height. Eight recreational female participants performed dominant and non-dominant single-leg drop landings from 30 to 60 cm. OpenSim software was used to develop participant-specific musculoskeletal models and to calculate muscle forces. We also predicted ACL loading using our previously established method. There were no significant differences between dominant and non-dominant leg landing except in ankle dorsiflexion and GMED muscle forces at peak GRF. Landing from a greater height resulted in significant differences among most kinetics and kinematics variables and ACL forces. Minimal differences in lower-limb muscle forces and ACL loading between the dominant and non-dominant legs during single-leg landing may suggest similar risk of injury across limbs in this cohort. Further research is required to confirm whether limb dominance may play an important role in the higher incidence of ACL injury in female athletes with larger and sport-specific cohorts.